Modification of optical and structural properties of manganese nanoparticles embedded samarium doped tellurite glass - Nurul Ainaa Najihah Busra, 1990-, author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2015